On the present state of the savings' bank question - Hancock, W. Neilson (Dublin Statistical Society, 1855)
About three years since, I had the honor of reading before this society a paper on the duties of the public with respect to charitable savings' banks. Since that time there have been promises of legislation, but nothing has been actually done to remove the general insecurity of the depositors to which I then directed attention. On the contrary, the recent statements of Mr. Gladstone, while Chancellor of the Exchequer, have disclosed some facts which will, I think, be as new to you as they were to me, and which place that insecurity in a still stronger point of view.
Read 19th February, 1855
Keywords: Savings banks; 314.15